Study of biomass particle combustion model to use in multi-particle simulation codes - Sousa, Nelson (2015)
This paper presents an analyses of the modelling specifications required in the simulation of the conversion of a single biomass particle to be used in multi-particles computer simulation codes. It considers the transport and reaction of gases, the heterogeneous combustion and heat transfer within the biomass. The biomass conversion is described by a competitive reaction mechanism specifying the composition of the volatile species and tar properties. This approach can represent the influence of the heating conditions on biomass conversion and produce acceptable compositions for the final products. Tar decomposition is considered within the particle as well as combustion reactions for all combustibles: volatile, tar and char. The study of several approaches show the level of numerical approach required to simulate the thermal conversion of the biomass particle and further reactions such as tar decomposition and oxidation of the combustibles gases within the particle. The validation of the numerical code is accomplished with the conversion of a 50 mm trunk in a hot gas stream by measuring the mass loss and temperature along the combustion process. Parametric tests are carried out to investigate the conversion of tars and oxidation of gases within the particle and it is concluded that these can be neglected for particle diameters smaller than 20 mm with an error less than 1%. For combustible particles such as wood chips and pellets with 6 mm diameter, all intern gradients may be neglected.